Ukraine pharmaceutical sector: current state of legal regulation - O. H. Aleksieiev (Zaporozhye State Medical University, 2020)
The purpose of the work. Analysis of the legislative support of the Ukraine pharmaceutical sector, the study of problematic issues of the legal protection of sectoral legal relations in order to formulate proposals for improving the legal protection of the rights of subjects of the Federal Security Service of Ukraine. Materials and methods. The study is based on the current regulatory framework of the pharmaceutical sector in the healthcare sector, as well as international regulatory acts regulating the circulation of medicines in EU countries. During the work, the methods of analysis of ATS synthesis, systematization and generalization were used. Results. The national sectoral regulatory framework of pharmacy is mostly aimed at securing the rights of citizens and streamlining public relations arising from the circulation of medicines, but at the same time requires constant improvement, which is caused by the dynamics of the development of public relations in the field of medicines circulation. The state strategy of implementation of the state policy of providing the population with medicines for the period up to 2025, directly notes that the current system of state regulation in the sphere of drug treatment does not fully meet the modern requirements, because the implementation of the legislation of Ukraine is not performed in all directions, and monitoring has no systemic. Conclusions. Legal regulation of Ukraine pharmaceutical sector is a state exercised by the law and the totality of legal means of ordering public relations that arise during the treatment of medicinal products and joint groups of relations with the purpose of their legal consolidation, protection, and development.